URTICA PILULIFERA AMELIORATES DIABETIC IMPACTS THROUGH UPREGULATION THE EXPRESSION OF HSP70 IN LIVER OF DIABETIC RATS - AlKhatib, Ahed J; Shah, Muhammad Syarmine; Alkhatatbeh, Mosleh A; AlKhatib, Ilham A; Maikano, A. B.; Shuaibu, S. M.; Sulaiman, M. A.; Abdulhadi, M.; Laiche, Fatima (European Scientific Journal, ESJ, 2014)
Diabetes has impacts in liver through downregulation of heat shock protein response. People used to use herbal remedies to treat diabetes among which is Urtica pilulifera (U. pilulifera). We conducted the present study to investigate the impacts of diabetes on liver through exploring the diabetic effects on expression of HSP70 in liver tissue and to explore the effects of the extract of U. pilulifera on liver of diabetic groups treated with U. pilulifera, and to investigate its effects on the expression of HSP70 in liver tissue. U. pilulifera was collected from various places in Jordan, air dried and extracted by Soxhlet cold extractor using absolute methanol as solvent and remained for three consecutive days. Extracted juice was kept in refrigerator at 4°C. Diabetes was induced through administration of alloxan 150 mg/kg body weight intraperitoneally. Study model included 4 groups: control group, diabetic group, diabetic group treated with 1.25 mg/kg body weight, and diabetic group treated with 1.88 mg/kg body weight. Study findings showed that diabetes downregulated the expression of HSP70 significantly in liver (P 0.000). There was a significant upregulation of HSP70 in diabetic groups treated with either dose of U. pilulifer (1.25 mg/kg of body weight, 1.88 mg/kg of body weight; P 0.000). Taken together, the present study demonstrated significant roles of using U. pilulifera in upregulating the expression of HSP70 in liver of diabetic rats. The induction of HSP response through U. pilulifera is unique, exciting, and inexpensive.